Requiem A Lament in three movements - Oden, Thomas C. (Nashville Abingdon Press, 1995)
"Requiem: a lament in three movements is a post-liberal critique of the mainline liberal ecclesiastical establishment, especially the theological seminaries and church bureaucracies. Thomas C. Oden identifies the failure of contemporary theological educ
Keywords: Oden, Thomas C. Liberalism (Religion) -- Protestant churches. Liberalism (Religion) -- United States